Ratik Basa Ritual Tulak Bala Di Nagari Singgalang X Koto Kabupaten Tanah Datar - Sabri Darmawan; Firdaus Firdaus; Muhammad Zulfahmi (Institut Seni Indonesia Padangpanjang, 2023)
The research entitled Ratik Basa as a Tulak Bala Ritual in Nagari Singgalang, X Koto District, Tanah Datar Regency, aims to describe the series of implementation of